Safety and Efficacy of Ustekinumab in the Treatment of Crohn Disease: A Systematic Review and Meta-analysis - Khorshid, Mohammed Assem; Cordie, Ahmed; Abd-Elsalam, Sherief (Journal of Coloproctology, 2022)
Background and Aims The present systematic review and meta-analysis was designed to estimate the safety and effectiveness of ustekinumab in the treatment of Crohn disease (CD) in clinical trials and observational studies.Methods We retrieved all the related publications from the PubMed, Cochrane, EBSCO, Google Scholar and EMBASE databases using a systematic search strategy. We only included clinical trials and observational studies that were published in English.Results Only 31 studies that met the eligibility criteria out of the 733 identified studies were included. The overall clinical response rate in the cohort studies was of 0.539 (95% confidence interval [95%CI]: 0.419–0.659), and in the clinical trials it was of 0.428 (95%CI: 0.356–0.501). The pooled clinical remission rate was of 0.399 (95%CI: 0.295–0.503) in randomized control trials (RCTs,) and of 0.440 (95%CI: 0.339–0.542) in cohort studies. The rate of adverse effects was of 0.158 (95%CI: 0.109–0.207) in cohort studies and of 0.690 (95%CI: 0.633–0.748) in RCTs.Conclusion Ustekinumab is effective in the treatment of CD. However, more research is required on the safety profiles because there was considerable variation among the included studies.
Keywords: Crohn Disease; inflammatory bowel disease; interleukin; cytokine; biologics